2007
DOI: 10.1097/nrl.0b013e3180f60bd8
|View full text |Cite
|
Sign up to set email alerts
|

Dextromethorphan as a Potential Neuroprotective Agent With Unique Mechanisms of Action

Abstract: Given the compelling preclinical evidence for neuroprotective properties of DM, initial clinical neuroprotective findings, and clinical demonstrations that the DM/Q combination is well tolerated, this strategy may hold promise for the treatment of various acute and degenerative neurologic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 103 publications
(262 reference statements)
1
64
0
Order By: Relevance
“…DM has already proven its therapeutic potential in different neonatal brain damage models like excitotoxicity and hypoxiaischemia [204][205][206] . It has numerous neuroactive properties including high-affinity σ1 receptor agonism, lowaffinity N-methyl-D -aspartate receptor (NMDAR) antagonism, and voltage-gated calcium channel antagonism, with additional anti-inflammatory and antioxidative qualities [207] . In 6-day-old rats exposed to 24 h of hyperoxia, a single dose (5 or 25 μg/kg of body weight) of DM significantly reduced apoptosis on immunohistochemistry.…”
Section: Hormonesmentioning
confidence: 99%
“…DM has already proven its therapeutic potential in different neonatal brain damage models like excitotoxicity and hypoxiaischemia [204][205][206] . It has numerous neuroactive properties including high-affinity σ1 receptor agonism, lowaffinity N-methyl-D -aspartate receptor (NMDAR) antagonism, and voltage-gated calcium channel antagonism, with additional anti-inflammatory and antioxidative qualities [207] . In 6-day-old rats exposed to 24 h of hyperoxia, a single dose (5 or 25 μg/kg of body weight) of DM significantly reduced apoptosis on immunohistochemistry.…”
Section: Hormonesmentioning
confidence: 99%
“…Innovation in this field is therefore a high priority. Treatment with dextromethorphan and quinidine has been proposed due to their mechanistic antagonism of nicotinic α3β4 receptor and low-affinity N -methyl-D-aspartate and inhibition of serotonin and norepinephrine reuptake,4 in addition to preliminary evidence of benefit to agitation in other patients.…”
Section: Contextmentioning
confidence: 99%
“…Significantly, more recent double-blind trials have confirmed that DM can improve motor function in PD patients, especially the dyskinesia associated with long-term levadopa treatment (Verhagen Metman, Blanchet et al 1998;Verhagen Metman, Del Dotto et al 1998). It has been suggested that the uncertainty over the true effects of DM might be due to the relatively rapid metabolism of DM in vivo (Werling, Lauterbach et al 2007). Although, DX and other DM metabolites have shown similar neuroprotective properties in preclinical studies, only DM seems to function through multiple mechanisms rather than simply blocking activity of the NMDA-receptor (Werling, Lauterbach et al 2007).…”
Section: Morphinan-based Anti-inflammatory Therapeuticsmentioning
confidence: 99%
“…It has been suggested that the uncertainty over the true effects of DM might be due to the relatively rapid metabolism of DM in vivo (Werling, Lauterbach et al 2007). Although, DX and other DM metabolites have shown similar neuroprotective properties in preclinical studies, only DM seems to function through multiple mechanisms rather than simply blocking activity of the NMDA-receptor (Werling, Lauterbach et al 2007). In situ DM concentrations can be increased if given in conjunction with a low dose of the drug quinidine which retards metabolism of DM and leads to increased DM concentrations in plasma, resulting in greater bioavailability (Pope, Khalil et al 2004).…”
Section: Morphinan-based Anti-inflammatory Therapeuticsmentioning
confidence: 99%